2012
DOI: 10.1093/fampra/cms036
|View full text |Cite
|
Sign up to set email alerts
|

Patients' views about the use of their personal information from general practice medical records in health research: a qualitative study in Ireland

Abstract: Overall male and female patients of different ages are supportive of the use of their general practice records in health research and of general practitioners as data protectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(77 citation statements)
references
References 15 publications
2
75
0
Order By: Relevance
“…Earlier studies on this subject have found that generally the support for health research is high. [ 29 31 ] Privacy protection is a common concern, and the risks involving research use of personal data are recognized. [ 19 , 29 , 31 33 ] The results have, nevertheless, shown the public has been willing to allow the use of their information and to consider alternative methods for study-by-study consent.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies on this subject have found that generally the support for health research is high. [ 29 31 ] Privacy protection is a common concern, and the risks involving research use of personal data are recognized. [ 19 , 29 , 31 33 ] The results have, nevertheless, shown the public has been willing to allow the use of their information and to consider alternative methods for study-by-study consent.…”
Section: Introductionmentioning
confidence: 99%
“…An interesting finding in our analysis is the discussion raised by researchers in Ireland regarding the attitudes of the public and patients towards the use of PHR data for health research (Buckley et al, 2011;Clerkin et al, 2013). Early PHR adopters would appear to be more willing to share their medical data for research .…”
Section: Discussionmentioning
confidence: 87%
“…The authors in this set present PHR innovations and prototypes [e.g., Bonander and Gates (2010), Seldon (2014) and Seldon et al (2014) and address function and research issues on data safety and security, such as encryption [e.g., Li et al (2013) and Wang et al (2012)], medical data sharing and access control [e.g., Li et al (2010) and ]. An interesting sub-theme also discusses attitudes among the public and patients towards the use of PHR data for health research (Buckley et al, 2011;Clerkin et al, 2013).…”
Section: (F1) Operation Of Phrs: Innovations Prototypes Data Governmentioning
confidence: 99%
“…For example, would a victim of domestic abuse really be able to prevent the perpetrator from accessing their records to find out their history or what they may have said to the doctor about them [43]? However despite this, patients are generally positive towards the idea of data from their records (anonymous and identifiable) being used in research for the 'greater good' [44].…”
Section: Patients' Perspective On Hcps Access To Their Emrmentioning
confidence: 99%